Beyond the bell : 12 lessons for navigating your life after high school - Pyrch, Melissa (Gildan Media LLC aka G&D Media, 2022)
"You're a graduate with a diploma and dream or no clue what do do next? Looks like you still have one more book to read. This one. Get ready to grow up and show up for your life Beyond the Bell"--Page 4 of cover.